1995
DOI: 10.1007/bf00170589
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal food availability on offspring dispersal

Abstract: Prenatal effects caused by the maternal environment during gestation are known to contribute to the phenotype of the offspring. Whether they have some adaptive value is currently under debate. We experimentally tested the existence of such a maternal effect (food availability during gestation) on dispersal of offspring in the common lizard (Lacerta vivipara).Pregnant females were captured and kept in the laboratory until parturition. During this period, females were offered two rates of food delivery. After pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 43 publications
1
78
3
Order By: Relevance
“…A review of stream insect response to predation showed however that increased or decreased emigration behaviours can be expected depending on the prey and predator species [63]. On the other hand, maternal effects have shown to influence offspring dispersal [25,[65][66][67][68]. For example, a differential transfer of maternal yolk androgens in response to parasitism has been shown to modify offspring dispersal in great tits [65].…”
Section: Discussionmentioning
confidence: 99%
“…A review of stream insect response to predation showed however that increased or decreased emigration behaviours can be expected depending on the prey and predator species [63]. On the other hand, maternal effects have shown to influence offspring dispersal [25,[65][66][67][68]. For example, a differential transfer of maternal yolk androgens in response to parasitism has been shown to modify offspring dispersal in great tits [65].…”
Section: Discussionmentioning
confidence: 99%
“…In the common lizard, parasitized mothers produce more philopatric female offspring (26). Conversely, in the same species, well fed mothers produce a larger fraction of dispersing offspring, with no sex effect (14). However, there are alternative explanations for these observed patterns of dispersal, such as a differential cost of producing dispersing and resident offspring.…”
Section: Generalization: Maternal Quality As a Source Of Habitat Hetementioning
confidence: 99%
“…We first suppose that the species is parthogenetic or that the species reproduces sexually but offspring movement is under maternal genotype control. Maternal control of seed dispersal is obvious in plants, and several cases of maternal effects on offspring dispersal have been reported in animal species (13)(14)(15)(16). We later relax this assumption and consider a species reproducing sexually in which juveniles control their own dispersal behavior.…”
Section: A Theoretical Model Of Age-dependent Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we show that parental influence on offspring dispersal distance is as important as the offspring's environment on dispersal decisions [22,53]. Parents can use a cue that normally promotes dispersal, such as density, and transmit that information to their offspring so that the offspring have a 'head-start' in their response to their own environmental conditions.…”
Section: Discussionmentioning
confidence: 88%